PERSONNEL MANAGEMENT SYSTEM OF AN EDUCATIONAL ORGANIZATION - Niso Y. Panoeva (International Scientific and Current Research Conferences, 2022)
The article analyzes the concept of management, the role of management in working with personnel, an analysis of the specifics of the teaching staff is carried out, and the main scientific approaches to working with the teaching staff are described.